2013
DOI: 10.1016/j.jbi.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Intervention time prediction from surgical low-level tasks

Abstract: The predictions can be used by the OR staff, the technical infrastructure of the OR, and centralized management. The predictions also support intervention scheduling and resource management when resources are shared among different operating rooms, thereby reducing resource conflicts. The predictions could also contribute to the improvement of surgical workflow and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 19 publications
0
37
0
Order By: Relevance
“…The framework included processors for generalized surgical process models (gSPMs) [1,3] and process models based on Hidden Markov Model theory. Additional modules for comprehensive logging, connection to an OR bus [5], intervention time prediction [3] and process information visualization [4] were incorporated. Furthermore, a prototypical network configuration for neurosurgical brain tumour removal was designed and implemented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The framework included processors for generalized surgical process models (gSPMs) [1,3] and process models based on Hidden Markov Model theory. Additional modules for comprehensive logging, connection to an OR bus [5], intervention time prediction [3] and process information visualization [4] were incorporated. Furthermore, a prototypical network configuration for neurosurgical brain tumour removal was designed and implemented.…”
Section: Resultsmentioning
confidence: 99%
“…The main use cases were information presentation [4], automatic configuration and orchestration of medical device functionalities [5], documentation, resource management and OR scheduling [3]. Each application required surgical process information.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The implemented prototype also provided predictions. Estimated probabilities of upcoming activities, qualitative assumptions on the usage of several devices and a prediction of the remaining intervention time [19] were included in the process-related information entities.…”
Section: Methodsmentioning
confidence: 99%
“…Using the da Vinci Research kit [33], [34], it has been shown in a clinical environment that subtask automation is feasible [35], and SPMs were used to integrate automated robotic intraoperative imaging [36]. Another aspect of workflow monitoring is OR workflow scheduling [37]. Since OR time is one of the most expensive resource of the hospital, by monitoring the workflow, it becomes possible to predict the duration of the surgery, as well as optimizing future procedure plans [14].…”
Section: A Context-aware Automation and Assistancementioning
confidence: 99%